(untitled) (TAJ: Journal of Teachers Association, 2011)
Arsenic is one of the important chemical water pollutants and number of arsenicosis patient in Bangladesh is remarkable. This cross-sectional study was done in several rural localities of Chapai Nawabganj with the view to find out the preventive measures adopted by the rural people to alleviate health problems of consuming arsenic contaminated ground water, and to determine the prevalence of chronic arsenicosis along with the proportion of people still consuming arsenic contaminated drinking water. The study areas were selected purposively and data were collected by a pre-tested questionnaire from 384 rural people sampled by systematic random sampling technique. Majority of the respondents were male. Among them 81.25% knew the arsenic as a pollutant of ground water and 79.17% had knowledge about the health problems due to it. Among the respondents, 83.33% were using arsenic contaminated water, in them only 97 (30.31%) had adopted preventive measures. Eighteen (4.69%) arsenicosis patients were found in the studied houses. A large section of people had knowledge about arsenic and its health problems. In rural areas many households were using arsenic contaminated water without getting any preventive measures. The number of arsenicosis patients is also remarkable. Provision of availability of arsenic free safe water and appropriate technology to make water arsenic free in that area is essential. Health education program should be initiated to encourage people about these. It also needs general education and financial conditional improvement. doi: 10.3329/taj.v19i1.3160 TAJ 2006; 19(1): 1-9